Prehospital critical care dispatch: a scoping review (PHASE) - Peter Owen; Kim Kirby; Julian Hannah; Robert Crouch; Philip Hyde; Sarah Voss (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Introduction Prehospital critical care (PHCC) dispatch is a vital component of emergency medical services, aiming to allocate specialised resources for critically ill or injured patients in out-of-hospital settings. This scoping review examines the existing evidence on optimising PHCC dispatch, identifies research gaps, and highlights priorities for future investigation. Methods A systematic search of databases including CINAHL, PubMed, EMBASE, and CENTRAL from January 2004 to October 2024. We included all study types, focusing on the dispatch of PHCC assets globally. Results The search yielded 39 studies that met the inclusion criteria. The included studies varied in design, setting and focus (e.g. Traumatic vs. Medical aetiology). Outcomes measured ranged across dispatch factors, physiological and temporal variables, with advanced intervention and survival metrics commonly used to asses dispatch effectiveness. Discussion The review found variability in dispatch models, staffing, and outcome measures. Most studies focused on HEMS and P-HEMS, often using injury mechanisms and physiological parameters as dispatch criteria. However, their predictive accuracy is inconsistent, especially for older trauma patients. Clinician involvement improves accuracy, but the role of cognitive tools needs more study. Challenges include ethical and logistical issues in prospective studies, limited research in low- and middle-income countries, and lack of harmonised datasets for missed dispatch opportunities. Technologies like automated crash notifications and real-time video show promise but need more development validation. Conclusion This review underscores the need for robust, prospective research to refine dispatch criteria and integrate advanced technologies. Addressing these gaps could improve resource allocation, reduce over- and under-triage, and ultimately enhance patient outcomes in PHCC systems.